A introdução da cláusula de barreira no sistema proporcional brasileiro: análise do contexto e dos impactos da alteração legislativa - Gabriel Amaral Rocha Ferreira (2020)
The present research aimed to investigate, after the introduction of the barrier clause by the Law n. 13.105 of 2015, in what way the introduction of such mechanism of access control to Legislative seats has improved the proportional representation system and if, according to the desires of those who defended the barrier clause introduction, it has eliminated the figure of a vote puller. The operation and of what can be expected of an electoral system was comprehended by the theory of Dieter Nohlen (2008; 2012) about the electoral systems in their contexts. Also, in order to understand the Brazilian case, especially the open list proportional representation system, it were used the conceptions of Jairo Nicolau (2004; 2006a; 2006b; 2015; 2017), along with the work of others classic and present-day authors about the way the Brazilian’s proportional representation system works. The figure of a vote puller candidate was comprehended by the analysis of Rodolfo Viana Pereira and Lucas de Oliveira Gelape (2015), regarding it’s characteristics, and also the results and impact caused by this kind of candidate in an electoral process. In order to analyze the impacts caused by the legislation modification, which is the introduction of the barrier clause on the Brazilian’s proportional representation system, an empiric investigation was carried on, by a data collection in the Superior Electoral Court and the Locals Electoral Courts about the 2010’s, 2014’s and 2018’s general elections, comparing then with each other for the purpose of check, in first place, if and in what way the modification in the system’s operation has improved the quality of democracy or improved the political representativity and, at second, the figure of a vote puller candidate was eliminated, popular known as “Tiririca effect”. The logic of the research was to collect, understand and compare concrete data, gathered by empirical research, based on the theorical foundations and utilized authors in order to sustain the interpretation which it was concluded. At last, based on the essay of Eneida Desiree Salgado (2018) about the political reforms made in Brazil, which questioned about who implement the reforms, how, for whom and why, it was concluded that the introduction of the barrier clause didn’t attended to the modification supporters’ expectations, which was to eliminate the figure of the vote puller, and also didn’t improve the way Brazilian’s proportional representation system works, regarding Hanna Pitkin’s (1983) concept of representativity, considering that the impacts caused by vote puller candidates in 2018 (after the introduction of the barrier clause) were bigger than some previous cases, like 2010’s and 2014’s elections, what was proved by the data collected and comprehended during the conduction of the present research.